Intrinsic and extrinsic factors contributing to running-related lower limb injuries among adolescent runners - DeJong Lempke, A. F.; Whitney, K. E.; Collins, S. E.; Hemecourt, P. A.; Meehan, W. P. (Journal of Sports Sciences, 2022)
The purpose of this study was to assess which combination of intrinsic and extrinsic factors contribute to running-related injury (RRI)among adolescent cross-country, track, and long-distance runners. We conducted a retrospective study at a hospital-affiliated sports injury prevention centre of 130 adolescent runners (F: 62.1%, M: 37.9%; cross-country: 34.1%, track: 56.1%, long-distance running: 9.8%) who underwent an Injury Prevention Evaluation between 2013 and 2021. The evaluation included a questionnaire on personal and training factors, and standardised physical assessments. We used a binomial logistic regression to assess the influence of demographics, lower extremity strength and alignment, training (running volume and intensity, weight training), and dietary factors on RRIs. There were 38 adolescent runners who reported RRIs (ankle sprains: N = 16, shin splints: N = 9, stress fractures: N = 13). Female sex (odds ratio [OR]: 4.58 [1.37, 15.37]; p = 0.01), reduced weekday hours of sleep (OR: 1.75 [1.04, 2.95]; p = 0.04), reduced hip abduction strength (OR: 1.02 [1.00, 1.04]; p = 0.05), and intention to lose weight to improve athletic performance (OR: 4.58 [1.00, 21.28]; p = 0.05) were associated with RRIs. These intrinsic and extrinsic risk factors may represent targets for injury prevention for adolescent runners.